Cyclin‐dependent kinase 5 promotes the growth of tongue squamous cell carcinoma through the microRNA 513c‐5p/cell division cycle 25B pathway and is associated with a poor prognosis. Issue 9 (10th February 2022) - Li, Yixuan; Yao, Fan; Jiao, Zan; Su, Xuan; Wu, Tong; Peng, Jin; Yang, Zhongyuan; Chen, Weichao; Yang, Ankui
Abstract : Background: The objective of this study was to investigate the role and molecular mechanism of cyclin‐dependent kinase 5 (CDK5) in regulating the growth of tongue squamous cell carcinoma (TSCC). Methods: The authors used multiple methods to detect the levels of CDK5 expression in samples of TSCC and to explore the relation between CDK5 expression and various clinicopathologic factors. In vivo and in vitro cell experiments were performed to detect the proliferation, invasion, and migration of TSCC cells with CDK5 knockdown or overexpression. These studies verified that CDK5 regulates the occurrence and development of TSCC cells through the microRNA 513c‐5p/cell division cycle 25B pathway. Results: An elevated level of CDK5 expression in TSCC tissues was identified as an independent risk factor affecting TSCC growth and patient prognosis. Patients who had TSCC with low levels of CDK5 expression had a higher survival rate than those with high levels. Knockdown of CDK5 reduced the proliferation, migration, and invasion of TSCC cells both in vitro and in vivo. In addition, the authors observed that CDK5 regulated the growth of TSCC through the microRNA 513c‐5p/cell division cycle C25B pathway. Conclusions: CDK5 functions as an oncogene in TSCC and might serve as a molecular marker for use in the diagnosis and treatment of TSCC. Lay Summary: Tongue squamous cell carcinoma (TSCC) is 1 of the most common malignant tumors of the head and neck, and the survival rate of patients with tongue cancer has been very low. Therefore, it is important to study the molecular mechanism of TSCC progression to identify biomarkers that can be used to improve its clinical diagnosis and treatment. Cyclin‐dependent kinase 5 (CDK5) is an atypical member of the cyclin‐dependent kinase family and is involved in regulating the cell cycle. Changes in the cell cycle are of great significance for the occurrence and development of tumor cells; and, in recent years, increasing evidence has suggested that CDK5 exists in a disordered state in cancer cells. In this study, the authors demonstrate that CDK5 functions as an oncogene in TSCC and might serve as a molecular marker for use in the diagnosis and treatment of TSCC. Abstract : The role of cyclin‐dependent kinase 5 and its molecular mechanism in regulating the growth of tongue squamous cell carcinoma (TSCC) are investigated. The results indicate that cyclin‐dependent kinase 5 is involved in the occurrence and development of TSCC and could possibly serve as a new prognostic marker and molecular target for treating TSCC.